Tubulin tyrosine nitration regulates microtubule organization in plant cells - Blume, Yaroslav B.; Krasylenko, Yuliya A.; Demchuk, Oleg M.; Yemets, Alla I. (Frontiers in Plant Science, 2013)
During last years, selective tyrosine nitration of plant proteins gains importance as well-recognized pathway of direct nitric oxide (NO) signal transduction. Plant microtubules are one of the intracellular signalling targets for NO, however, the molecular mechanisms of NO signal transduction with the involvement of cytoskeletal proteins remain to be elucidated. Since biochemical evidence of plant α-tubulin tyrosine nitration has been obtained recently, potential role of this posttranslational modification in regulation of microtubules organization in plant cell is estimated in current paper. It was shown that 3-nitrotyrosine (3-NO2-Tyr) induced partially reversible Arabidopsis primary root growth inhibition, alterations of root hairs morphology and organization of microtubules in root cells. It was also revealed that 3-NO2-Tyr intensively decorates such highly dynamic microtubular arrays as preprophase bands, mitotic spindles and phragmoplasts of Nicotiana tabacum (BY-2) cells under physiological conditions. Moreover, 3D models of the mitotic kinesin-8 complexes with the tail of detyrosinated, tyrosinated and tyrosine nitrated α-tubulin (on C-terminal Tyr 450 residue) from Arabidopsis were reconstructed in silico to investigate the potential influence of tubulin nitrotyrosination on the molecular dynamics of α-tubulin and kinesin-8 interaction. Generally, presented data suggest that plant α-tubulin tyrosine nitration can be considered as its common posttranslational modification, the direct mechanism of NO signal transduction with the participation of microtubules under physiological conditions and one of the hallmarks of the increased microtubule dynamics.